Management Analysis of Covid-19 Prevention and Control at Public Health Center in Musi Rawas Utara Regency - Haryanti, Nelly; Novrikasari, Novrikasari; Syakuroh, Rizma Adlia (Budapest International Research and Critics University, 2021)
This study aims to analyze in depth the factors, effectiveness, constraints, and efforts to prevent and control the COVID-19 pandemic at the public health center in Musi Rawas Utara Regency, viewed from the management system. The method of study is qualitative research. The research was carried out through observation, document review, and in-depth interviews. The informants are the Head of Public Health Center, the person in Charge of the COVID-19 prevention and control (PC) program at the public health center, the COVID-19 prevention and control (PC) Team and the doctor in charge of health service activities. Data analysis according to Miles, Huberman, and Saldana's theory, which consists of three steps: data condensation, data display, and conclusion drawing and verification. Results: The factors for implementing the prevention and control of the COVID-19 pandemic at public health centers in Musi Rawas Utara Regency are five factors, namely human resources, facilities and infrastructure, budget or funds, IPC methods and policies. The effectiveness of the implementation of the prevention and control of the COVID-19 pandemic at the public health centers in Musi Rawas Utara Regency, which is viewed from the management system consisting of planning, organizing, implementing, and monitoring the five factors above, is generally effective.